The Multiple Lives of Translators - Meylaerts, Reine (TTR)

(untitled) (Association canadienne de traductologie, 2013)
Daniel Simeoni’s call for an actor-based complement to the concept of norms in Translation Studies and its subsequent introduction of the habitus concept has revealed groundbreaking. Among other things, Translation Studies has benefited from using habitus as a conceptual tool to comprehend the translator/interpreter as a professional. However, as already pointed out by Simeoni 1998, a translator’s habitus cannot be reduced to his/her professional expertise as a translator. The present essay takes this observation a step further and argues that a translator’s plural and dynamic habitus (Lahire, 2004) also stands for a socialized individual with various positions and perceptions in other fields (e.g. the literary field for a literary translator especially when he/she is a novelist or critic him/herself) of which it would be artificial to isolate the translatorial habitus. A nuanced understanding of literary translators’ self-images and roles in cultural history asks for fine-grained analyses of their dynamic and plural intercultural habitus in all its complexities. It will lay bare translators’ multipositionality across linguistic, national and field-specific boundaries and the perceived aims, forms and functions of their multiple transfer activities, e.g. for the establishing of a national or international culture. Such an analysis may also contribute to a renewed model for interdisciplinary and intercultural historiographies of culture embedding translation within a multitude of transfer activities (translation, self-translation, etc.). As an illustration hereof, this essay analyzes a literary translator’s habitus in early 20th century Belgium.